Comparative studies on the characteristic properties of the ground and conventional LaCo0.7Cu0.3O3 perovskite - Thao, Nguyen Tien; KALIAGUINE, SERGE (Vietnam Journal of Chemistry, 2014)
The characteristics of two perovkites and a blend of mixed oxides prepared by reactive grinding and citrate complex method have been comparatively investigated using several techniques (X-ray, BET, H2-TPR, chemisorption, O2-TPD). XRD results confirm the successful substitution of Co by Cu in the lattice of La(Co,Cu)O3 perovkite. The ground materials with smaller particle sizes and larger surface area show more thermal stability than does the citrate-derived sample under the same reducing conditions. Due to a lower surface area and nonporous structure, the conventional sample adsorbed a smaller amount of oxygen on the surface sites and on the vacancies compared with the other catalysts.